The effect of using the seven-course learning cycle strategy in learning the scoring skill from the free throw line and the peaceful throwing line with basketball (Journal of the College of Basic Education, 2022)
The research included four chapters in Chapter One that included the introduction, the importance of the research, the problem of research, and the objectives of the research, namely:-Preparing special educational units using the seventh learning cycle strategy in learning the scoring skill from the free throw and peaceful line with basketball.-Knowing the effect of using the strategy of the seventh learning in learning the scoring skill from the free and peaceful throw line with basketball.Knowing which of the two groups is the best search for learning the scoring skill from the free-throw and ladder line with basketball.And research hypotheses and areas of research. The second chapter includes the research methodology, in which the researchers used the experimental method and the sample, and they are middle school students, fourth grade of middle school, which is (60) students, and it is divided into an experimental group (30) students (30) students of the control group. Educational units, after which the post tests were conductedThe third chapter includes the presentation, analysis and discussion of the results and the most important conclusions reached by the research mechanism-The use of the strategy of the seven-course learning cycle according to complex exercises has a positive effect on learning the skill of scoring, free throw line, and peaceful scoring with basketball for students of the experimental group.-The results showed that the use of the Es7 learning cycle strategy and the educational program had a positive effect on skill, free throw line scoring, and peaceful scoring with basketball for the experimental group